Quality of Life Improves with Alemtuzumab Over 6 Years in Relapsing-Remitting Multiple Sclerosis Patients with or without Autoimmune Thyroid Adverse Events: Post Hoc Analysis of the CARE-MS Studies - Bertolotto, Antonio; Arroyo, Rafael; Celius, Elisabeth G; Comi, Giancarlo; Havrdova, Eva Kubala; Honeycutt, William David; Hunter, Samuel F; Izquierdo, Guillermo; Kornek, Barbara; Miller, Tamara; Mitsikostas, Dimos D; Singer, Barry A; et al. (Neurology and therapy, 2020)
INTRODUCTION: In clinical trials of alemtuzumab, autoimmune thyroid adverse events (AEs) were frequent. Here, we assess the impact of thyroid AEs on health-related quality of life (HRQL) in alemtuzumab-treated patients with relapsing-remitting multiple sclerosis (RRMS). METHODS: In phase 3 CARE-MS I (NCT00530348) and II (NCT00548405) trials, patients with RRMS were administered alemtuzumab 12 mg/day on 5 consecutive days at baseline and on 3 consecutive days 12 months later. Patients could participate in an extension study (NCT00930553) through year 6. HRQL was assessed at baseline and annually using the Functional Assessment of Multiple Sclerosis (FAMS), EuroQoL-5 Dimension Visual Analog Scale (EQ-5D VAS), and 36-Item Short-Form Survey (SF-36) questionnaires. Outcomes were analyzed in patients with or without thyroid AEs (nonserious or serious). A subset of patients with thyroid AEs was analyzed to assess HRQL before and during the onset of thyroid AEs. RESULTS: A total of 811 CARE-MS patients were treated with alemtuzumab. Of these, 342 (42%) patients experienced thyroid AEs over 6 years; serious thyroid AEs occurred in 44 (5%) patients. At year 6, HRQL outcomes generally remained slightly improved or similar to core study baseline in alemtuzumab-treated patients with or without thyroid AEs: FAMS (least-squares mean change from baseline without thyroid AEs, 0.7; with nonserious thyroid AEs, 5.1; with serious thyroid AEs, - 5.3), EQ-5D VAS (2.0; 3.0; - 6.8), SF-36 mental component summary (MCS [0.6; 1.6; - 2.8]), SF-36 physical component summary (PCS [0.8; 1.0; 1.1]). Over 6 years, 63-82% of patients in each group had improved/stable SF-36 MCS and PCS scores. Among patients with thyroid AE onset in year 3 (peak incidence), there were minimal differences between HRQL outcomes before onset (year 2) and after onset (year 3). CONCLUSION: Autoimmune thyroid AEs (serious and nonserious) had minimal impact on HRQL in alemtuzumab-treated patients. These data may aid therapeutic decisions in patients with relapsing MS.
Keywords: Thyroid adverse events; Relapsing-remitting multiple sclerosis; Health-related quality of life; Alemtuzumab